The Advent of Open Source Democracy and Wikipolitics: Challenges, Threats and Opportunities for Democratic Discourse - Kostakis, Vasilis (Human Technology, 2011)
It has been claimed that the Web 2.0, the open source movement, and the emerging mode of peer production have inaugurated a new era of debate about openness, participation, and cooperation as bedrocks for rebuilding the civilizations of the modern world. By way of introducing the concept of wikipolitics, this paper examines whether, and if so how, politics and democracies can benefit from this emerging participatory spirit and modern ICTs, and to document possible dangers of such a shift in the democratic process.